Aplicación de contabilidad comercial por el método de cuenta permanente en el “Comercial Ferretería López” de la parroquia los encuentros, cantón Yantzaza, periodo: marzo – mayo/2015 - Macas Chamba, Jhoana Elizabeth (2016)
This research work was carried out with the purpose of providing technical input - the commercial accounting HARDWARE Lopez to improve the economic performance of the hardware as well as being an indispensable prior to choose the degree of Engineer in Accounting and Auditing requirement. Since the owner benefits from knowing the relevant procedures for adequate control of the resources available, to I cut wasteful spending and thus gradually increase their profitability and corporate reputation, earned through years in the market. Its implementation contributes to comply with the proposed objectives and referring to implement accounting in the business; performing the accounting process from the Chart of Accounts, User Accounts, Home Inventory, State Initial Situation, Daybook, Ledger, Trial Balance and Financial Statements, demonstrating clearly and realistically the results obtained in the period; conducting further statements of the company at the end of the period established for the purpose of avoiding tax penalties fall into the IRS is presented. Once applied the accounting process, it is concluded that the practical application yielded real results through financial statements, so it is recommended to implement accounting as a tool that helps to have better control of the operations carried out within the enterprise; this in order to increase business profitability obtained at the end of an economic cycle, in the medium or long term.